The Herbal Formula Granule Prescription Mahuang Decoction Ameliorated Chronic Kidney Disease Which Was Associated with Restoration of Dysbiosis of Intestinal Microbiota in Rats. (24th June 2021) - Ming, Yao; Cheng, Sijing; Long, Wen; Wang, Hong-Lian; Xu, Chuanlan; Liu, Xiaoyu; Zhang, Qiong; Zhao, Sha; Zou, Xia; Fan, Junming; Wang, Li; Shen, Hongchun
Abstract : Chronic kidney disease (CKD) has become a global health issue, and there is increasing evidence showing the beneficial roles of traditional Chinese medicine (TCM) in CKD treatment. Here, we studied the renoprotective role of Mahuang decoction, a famous TCM prescription, in a rat CKD model induced with the combination of doxorubicin and adenine. Our data showed that intragastric administration of Mahuang decoction inhibited the loss of bodyweight and attenuated proteinuria, serum creatinine, and blood urea nitrogen in CKD rats. Kidney histological analysis revealed decreased tubulointerstitial injury and fibrosis in CKD rats treated with Mahuang decoction accompanied with suppressed expression of TGF- β 1 and phosphorylated NF- κ B/P65 (p-P65) as indicated by immunohistochemistry. ELISA analysis demonstrated reduced serum levels of proinflammatory cytokines TNF α and IL-6. Most importantly, intestinal microbiota analysis by 16s rRNA-seq showed that Mahuang decoction restored the impaired richness and diversity of intestinal microflora and recovered the disrupted microbial community through reducing the abundance of deleterious microbes and promoting the expansion of beneficial microbes in CKD rats. Collectively, our findings demonstrated that Mahuang decoction mitigated kidney functional and structural impairment in CKD rats which were associated with the restoration of dysbiosis of intestinal microbiota, implying its potential in clinical CKD treatment.